Potential role of mitochondria and endoplasmic reticulum in the response elicited by D-aspartate in TM4 Sertoli cells - Falvo, Sara; Grillo, Giulia; Latino, Debora; Chieffi Baccari, Gabriella; Di Fiore, Maria Maddalena; Venditti, Massimo; Petito, Giuseppe; Santillo, Alessandra (Frontiers in Cell and Developmental Biology, 2024)
D-Aspartic Acid (D-Asp) affects spermatogenesis by enhancing the biosynthesis of the sex steroid hormones acting either through the hypothalamus-pituitary-testis axis or directly on Leydig cells.Recently, in vitro studies have also demonstrated the direct effects of D-Asp on the proliferation and/or activity of germ cells. However, although D-Asp is present in Sertoli cells (SC), the specific role of the amino acid in these cells remains unknown. This study investigated the effects of D-Asp on the proliferation and activity of TM4 SC, focusing on the mitochondrial compartment and its association with the endoplasmic reticulum (ER). We found that D-Asp enhanced the proliferation and activity of TM4 cells as evidenced by the activation of ERK/Akt/PCNA pathway and the increase in the protein levels of the androgen receptor. Furthermore, D-Asp reduced both the oxidative stress and apoptotic process. An increase in mitochondrial functionality and dynamics, as well as a reduction in ER stress, were also found in D-Asp-treated TM4 cells. It is known that mitochondria are closely associated with ER to form the Mitochondrial-Associated Endoplasmic Reticulum Membranes (MAM), the site of calcium ions and lipid transfer from ER to the mitochondria, and vice-versa. The data demonstrated that D-Asp induced stabilization of MAM in TM4 cells. In conclusion, this study is the first to demonstrate a direct effect of D-Asp on SC activity and to clarify the cellular/molecular mechanism underlying these effects, suggesting that D-Asp could stimulate spermatogenesis by improving the efficiency of SC.